Organic waste as an alternative feeds for pigs - Ramírez N., Viviana Marcela; Peñuela S., Lina María; Pérez R., María Del Rocío (Revista de Ciencias Agrícolas, 2017)
Food loss and food waste (LWF) are originated in field until their transformation and consumption, producing a negative impact in the natural resources (water and earth), and loss of nutrients (energy and proteins). LWF can be used in animal feeding through transformation and enrichment, favoring environmental conservation and leading to an “organic production”. Studies have been conducted characterizing nutritionally the LWF offered in different forms, proportion and mixture, as well as its relationship with animal performance, obtaining encouraging results of conversion, weight gain and reproductive performance.. Thus, this review presents some alternatives in the use of dish residues with alternatives that reduce the microbial load and its use in feeding pigs with values that have been favorable for production. In addition, silage has been proposed as a strategy for using LWFs, and as a low-cost alternative for peasant economies and sustainable production systems that are environmentally friendly.